Clonidine Does Not Reduce Pain or Opioid Consumption After Noncardiac Surgery. Issue 2 (April 2017) - Turan, A.; Babazade, R.; Kurz, A.; Devereaux, P. J.; Zimmerman, N. M.; Hutcherson, M. T.; Naylor, A. J.; Ali Sakr Esa, W.; Parlow, J.; Gilron, I.; Honar, H.; Salmasi, V.; et al.
Abstract : (Abstracted from Anesth Analg, 123:749–757, 2016) A multimodal technique using differing classes of nonopioid analgesics to reduce pain after surgery can improve recovery and reduce opioid requirements. Clonidine, an α2-adrenoceptor agonist, is often used as part of a multimodal analgesic technique.